Effect of Potassium Fertilization and Chamomile Extract Foliar Spray on Growth and Active Compounds of Portulaca Oleracea L. Grown in Gypsiferous Soil - Heba M. M. Al-Hamdany; Ahmed Adnan Mohammed; Suzan D. Hadi; Dalya Ayden Hawar (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2025)
The present study was conducted to investigate the effect of potassium fertilization and foliar application of chamomile extract on the growth and active compounds of Portulaca oleracea L. The experiment was carried out at the College of Medicinal and Industrial Plants / University of Kirkuk in the Ronaki area in Kirkuk Governorate using anvils. Four levels of potassium fertilizer (0, 20, 40, 80) kg K ha-1 and three concentrations of chamomile extract (0, 3, 6 g L-1 of water) were used on the growth of the portulaca plant L. oleracea. The variety used in this study is the local variety. The study was carried out with a factorial experiment and a randomized complete block design (R.C.B.D) with three replicates. The results showed that the fertilizer level of 40 kg K ha-1 was significantly superior to the rest of the levels in giving the highest plant height, number of leaves, leaf area, and other studied traits. The results also showed that the concentration (6 g L-1) of chamomile led to a significant increase in all growth characteristics of the barberry plant, while the interaction between potassium fertilization and spraying with chamomile extract had a significant effect at the combination (40 kg K ha-1 + 6 g chamomile L-1 of water) on all the studied traits.